DESAIN PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM PENGRAJIN ROTAN (STUDI PADA UMKM ANEKA ROTAN DI KOTA MANADO) - Hedy Desiree Rumambi; Revleen Mariana Kaparang; Grace Ropa; Haryanto Edward Setiadie (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
This study aims to design the cost production calculation of MSME  for rattan artisan. This research used  qualitative methods. We collected the data through in-depth interviews with MSME owners and literature studies. Data analysis used the stages of data reduction, data presentation, and design results. We started the design from MSME business activities by identifying production costs arising from the wreath frames production process and classifying the existing costs like raw material, direct labor, and factory overhead. The design used several assumptions, such as production cost is calculated for one production cycle, and there is no inventory for raw materials and work in progress. We used the full costing method to determine the product's cost. The use of these assumptions to make it easier for the owner in calculating the cost of production. Based on the financial transactions that occur, the wreath frame's production cost from 'Aneka Rotan' was Rp. 9.276.000,-